Influence of culture medium on the production of eif antigen from Leishmania chagasi in recombinant Escherichia coli - Santos, Everaldo Silvino dos (2011)
With the advent of recombinant DNA technology, recombinant protein expression has become an important tool in the study of the structure, function and identification of new proteins, especially those with therapeutic functions. Escherichia coli has been the predominant prokaryote used in genetic engineering studies due to the abundance of information about its metabolism. Despite significant advances in molecular biology and immunology of infections, there are as yet no prophylactic drugs capable of preventing visceral leishmaniasis. It is therefore important to identify specific antigens in order to develop vaccines and diagnostic kits against this disease. The objective of this study was to evaluate the influence of culture medium on the production of eIF antigen from Leishmania chagasi in recombinant Escherichia coli. An induction procedure using IPTG was carried out in a series of trials, to observe the influence of culture medium (2xTY, TB) under expression of the recombinant eIF protein. Results showed that recombinant protein expression was associated to growth and that the highest eIF antigen expression was obtained in the 2xTY medium